Self-Insurance and Self-Protection as Public Goods - Tim Lohse; Julio Robledo; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2010)
Most pure public goods like lighthouses, dams, or national defense provide utility mainly by insuring against hazardous events. Our paper focuses on this insurance character of public goods. As for private actions against hazardous events, one can distinguish between self-insurance (SI) and self-protection (SP) also in the context of public goods. For both cases of SI and SP we analyze efficient public provision levels as well as provision levels resulting from Nash behavior in a private provision game. An interesting aspect of considering public goods as insurance devices is the interaction with market insurance. It turns out that the availability of market insurance reduces the provision level of the public good for both, the public and the private provision, regardless of whether we consider SI or SP. Moreover, we show that Nash behavior has always a larger impact than the availability of market insurance.
Keywords: G22; H41; 330; Self-insurance; self-protection; private provision of public goods; market insurance